Distúrbios osteomusculares relacionados ao trabalho: avaliação da exposição ocupacional por meio de inclinometria e revisão sistemática sobre biomarcadores inflamatórios - Faturi, Fernanda Maria (Universidade Federal de São Carlos, 2014)
Background: Work-Related Musculoskeletal Disorders (WMSDs) are associated with biomechanical and psychosocial risk factors. Accurate assessment of exposure at work by means of direct measurement equipment allows risk factors identification. Selfreported questionnaires and inflammatory biomarkers can also be applied in this context. Therefore, two studies were conducted aiming to understand these aspects. Objectives: Study 1 aimed to describe the biomechanical exposure of the lumbar spine and shoulders in industrial workers and to correlate biomechanical and psychosocial aspects with functional and clinical indicators. Study 2 aimed to determine whether inflammatory biomarkers are altered in individuals with WMSD performing occupational activities or simulated tasks in the laboratory by means of a systematic literature review. Methods: In study 1 twenty eight male workers were evaluated by questionnaires related to musculoskeletal symptoms, disability and workplace stress. Inclinometers (Logger Tecknologi, Åkarp, Sweden) were used to assess the postures at work. In Study 2, a survey was conducted in the electronic databases including Medline, Science Direct, Web of Science, Scopus and CINAHL. The last survey was conducted in May 2013. Studies that investigated the relationship between inflammatory markers and WMSD in individuals who performed work activities or simulated tasks were selected. There were no restrictions regarding the language and date of publication. Results: Study 1 showed that workers showed slight flexion of the lumbar spine. The elevation of the shoulders reached values above 90° in less than 4% of the work time. The lunch break showed lower lumbar spine and shoulders angular velocity. Significant correlations were found between time in flexion greater than 15 and symptoms in the lumbar spine in the last 12 months, lumbar inclination and social support, velocity and shoulder symptoms in the last 12 months and control and shoulder symptoms. Active workers had higher proportion of shoulder symptoms in the past 12 months and workers with low strain sought health care for symptoms in the shoulders more often. In Study 2 the electronic search yielded 410 studies, of which nine met the inclusion criteria, five quasi-experimental and four observational. No experimental study was found. Four studies were considered high and five low methodological quality. Interleukin 6 was evaluated in eight studies, TNFα in six studies, interleukin1β in four studies, C-reactive protein in three studies and interleukins 8 and 10 in two studies. Thirteen other inflammatory markers were found in only one study each. Conclusion: Exposure of workers to postural risk factors were described. The angular velocity differentiate exposure of work and rest. Correlation between biomechanical, psychosocial and clinical factors were found. Psychosocial factors may interfere with the biomechanical exposure. In relation to inflammatory biomarkers, the level of evidence obtained was inconclusive because the results were inconsistent between studies. Standardization of measures and methodological improvements are strongly recommended.
Keywords: Fisioterapia; Trabalho; Lesões por esforços repetitivos; Inclinometria; Biomarcadores inflamatórios; Citocinas; Exposição ocupacional; Dor crônica; Postura; Estresse; Cumulative trauma disorders; Physical therapy in occupational health; Occupational exposure; Chronic pain; Posture; Inclinometry; Stress; Inflammation; Inflammatory biomarkers; Cytokines; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL